Model Team Accelerated Instruction (TAI) dengan Pendekatan Open-Ended Efektif Ditinjau dari Kemampuan Penalaran dan Self-Efficacy Siswa - Tri Andriyani; Raden Rosnawati (FKIP Universitas Mataram, 2026)
The purpose of this study is to describe the differences in the effectiveness of the TAI cooperative learning model with an open-ended approach and the conventional learning model in terms of students’ mathematical reasoning abilities and self-efficacy. This study is a quasi-experimental study using a nonequivalent comparison group design. The subjects of this study were 10th-grade students at a public high school in Yogyakarta. The sample consisted of two classes, each of which followed the TAI-type cooperative learning model with an open-ended approach and conventional learning, respectively. The research instruments consisted of a reasoning ability test and a self-efficacy scale. Data analysis techniques included descriptive and inferential analysis. The results of the study at a 5% significance level indicate that: 1) the TAI cooperative learning model with an open-ended approach is effective in terms of students’ mathematical reasoning ability and self-efficacy; 2) the conventional learning model is effective in terms of students’ mathematical reasoning ability and self-efficacy; 3) the TAI-type cooperative learning model with an open-ended approach is more effective than the conventional learning model in terms of students’ mathematical reasoning ability; however, there is no difference in effectiveness between the two models in terms of students’ self-efficacy.